2010
DOI: 10.1002/biot.201000091
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation influences on the aggregation propensity of therapeutic monoclonal antibodies

Abstract: Monoclonal antibodies are the fastest growing class of biologics in the pharmaceutical industry. The correlation between mAb glycosylation and aggregation has not been elucidated in detail, yet understanding the structure-stability relationship involving glycosylation is critical for developing successful drug formulations. We conducted studies of temperature-induced aggregation and compared the stability of both glycosylated and aglycosylated forms of a human IgG1. In parallel, we also performed molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(94 citation statements)
references
References 19 publications
3
91
0
Order By: Relevance
“…30 It is possible that the increased flexibility of the peptide backbone disrupts the packing interactions between the peptide backbone and the glycan chains, leading to unfolding of this hydrophobic segment. This unfolded apolar segment, in turn, may act as a hotspot for subsequent structural alterations that could lead to irreversible aggregation in IgG1 mAbs, [55][56][57] for example, as observed by SEC analysis in this study. Limiting the flexibility of this particular segment may therefore serve as a good indicator for designing mAbs (and mAbrelated products such as IgG-Fc, fusion proteins, or antibody drug conjugates) with higher thermostability and resistance to aggregation.…”
Section: Discussionmentioning
confidence: 57%
“…30 It is possible that the increased flexibility of the peptide backbone disrupts the packing interactions between the peptide backbone and the glycan chains, leading to unfolding of this hydrophobic segment. This unfolded apolar segment, in turn, may act as a hotspot for subsequent structural alterations that could lead to irreversible aggregation in IgG1 mAbs, [55][56][57] for example, as observed by SEC analysis in this study. Limiting the flexibility of this particular segment may therefore serve as a good indicator for designing mAbs (and mAbrelated products such as IgG-Fc, fusion proteins, or antibody drug conjugates) with higher thermostability and resistance to aggregation.…”
Section: Discussionmentioning
confidence: 57%
“…The percentage of aggregates, fragments and monomers from SEC chromatograms are plotted separately in Figure 7A-C. Figure 7A shows that all three antibodies exhibit higher aggregation rates after deglycosylation. 30 also mentioned that many hydrophobic residues masked by carbohydrate were exposed after deglycosylation. Both reports used molecular dynamics simulations during their analysis and suggested that the hydrophobicity change in the CH 2 domain played an important role during aggregate formation.…”
Section: Discussionmentioning
confidence: 99%
“…After successful purification and formulation, the questions remains whether the protein has been brought into its most stable form: to address this issue, the group of Bernhard Trout reports a predictive tool to determine proteins stability [17], which follows on from their previous report of an algorithm that demonstrates to what extent glycosylation of antibodies influences their stability [18].…”
Section: "Progress In Biotechnology Is a Results Of Its Interdisciplinmentioning
confidence: 99%